Operando Measurements of Electrolyte Li-ion Concentration during fast charging with FTIR/ATR. Issue 9 (6th September 2021) - Meyer, Lydia; Curran, David; Brow, Ryan; Santhanagopalan, Shriram; Porter, Jason
Abstract : The ability to charge a Li-ion battery at high charging rates is critical for electric vehicle adoption; however, further study of ion transport is required to develop electrolytes suitable for fast charge. Fourier transform infrared spectroscopy (FTIR) used with attenuated total reflection (ATR) enables operando measurements of liquid electrolytes. This research focused on solvation shifting of solvent infrared absorption bands in the presence of lithium ions. Lithium-shifted infrared absorption bands and non-shifted bands of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were compared to infer ion concentration changes during cycling. Lithium concentrations were calibrated using EC/EMC/LiPF6 electrolytes with known lithium concentrations. A Li-ion half-cell with a graphite anode and EC/EMC/LiPF6 electrolyte was observed with FTIR/ATR. The results showed that the magnitude of lithium concentration changes increased with increasing C-rate. During a galvanostatic intermittent titration technique (GITT) test, changes in lithium concentration could be observed. During intercalation, a lithium depletion occurred when a negative current was applied, and a lithium surplus occurred during deintercalation when a positive current was applied. The capability of observing lithium concentration has significant implications for the utility of operando studies and the potential to link lithium movement to battery performance.